Auschwitz, the allies and censorship of the Holocaust - Fleming, Michael (Cambridge University Press, 2014)
What was the extent of allied knowledge regarding the mass murder of Jews at Auschwitz during the Second World War? The question is one which continues to prompt heated historical debate, and Michael Fleming's important new book offers a definitive account of just how much the Allies knew. By tracking Polish and other reports about Auschwitz from their source, and surveying how knowledge was gathered, controlled and distributed to different audiences, the book examines the extent to which information about the camp was passed on to the British and American authorities, and how the dissemination of this knowledge was limited by propaganda and information agencies in the West. In a fascinating new study, the author reveals that the Allies had extensive knowledge of the mass killing of Jews at Auschwitz much earlier than previously thought; but the publicising of this information was actively discouraged in Britain and the US.